Face Masks Bolsters the Characteristics From Looking at a Face Even When Facial Expressions Are Impaired - Lau, Wee Kiat (Frontiers in Psychology, 2021)
Face masks impact social interactions because emotion recognition is difficult due to face occlusion. However, is this enough to conclude that face masks negatively impact social interactions? We investigated the impact of face masks on invariant characteristics (sex, age), trait-like characteristics (trustworthiness, attractiveness, approachability), and emotional expressions (happiness, excitability). Participants completed an online survey and rated masked and no-masked faces. The same face remained masked or no-masked throughout the survey. Results revealed that, when compared to no-masked faces, masked happy faces appeared less happy. Face masks did not negatively impact the ratings of other characteristics. Participants were better at judging the sex of masked faces. Masked faces also appeared younger, more trustworthy, more attractive, and more approachable. Therefore, face masks did not always result in unfavorable ratings. An additional post-hoc modelling revealed that trustworthiness and attractiveness ratings for masked faces predicted the same trait ratings for no-masked faces. However, approachability ratings for no-masked faces predicted the same trait ratings for masked faces. This hinted that information from masked/no-masked faces, such as from the eye and eye region, could aid in the understanding of others during social interaction. Future directions were proposed to expand the research.